Hell's Faire - Ringo, John (New York. Baen., 2003)
With the fall of the Southern Appalachian defenses, the only thing standing between the vulnerable Cumberland Plateau and the vicious Posleen hordes are the veterans of the 555th Mobile Infantry who, led by Mike O'Neal and armed with a top-secret weapon, are dropped into the Rabun Pass to risk everything on an all-out effort to stop the Posleen advance
85874
Keywords: Space warfare